Kreativitas Mahasiswa dalam Berkarya 3 Dimensi dari Barang Bekas pada Mata Kuliah SBdP Prodi PGMI IAI Hasanuddin Pare Kediri - Sri Putrianingsih (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2026)
This study aims to determine the increase in students’ creativity in making 3 dimensional works of art in SBdP subject using used goods. This study uses a qualitative reseach method with a descriptive type of approach which is intended to clearly describe the event that occurred whe the reseach was carried out. The subjects in this study were were 7th semester college students. Data collection techniques using observation, interviews, and documentation. Respondents used in this study amounted to 42 college students and 1 SBdP lecturer.based on the results of the research that used good can increase student’ creativity in making 3 dimensional works of art.